Normative and Institutional Foundations of Modern State Policy Regarding Complainers Abroad - Nikitina, Elena; Tarbeeva, Irina; Vasileva, Elena; Zerchaninova, Tatiana (KnE Social Sciences, 2021)
Currently, about 30 million [8] compatriots live in the world who finds themselves outside of Russia. The collapse of the USSR and the formation new independent states saw millions of Russian people separated from Russia by borders, and faced discrimination on the basis of language, which caused an increase in the migration activity of the Russian population in the post-Soviet space. This situation requires a review of the principles and directions state authorities’ activity in the migration sphere and determination of the necessary regulatory legal framework for regulating the processes of the influx of migrants from the former Soviet republics to Russia. The purposes of the research are 1) to study the regulatory and institutional foundations of modern public policy in relation to compatriots abroad and 2) to identify its main directions. The main research method is the analysis of official documents, regulatory legal acts, reporting and analytical documents of authorities implementing the state policy regarding compatriots living abroad. The state policy of the Russian Federation regarding expatriate citizens is a system of legal, diplomatic, social, economic, and organizational measures aimed at supporting and protecting Russian compatriots, ensuring the exercise of their rights and legitimate interests, as well as creating conditions under which they could would live as equal citizens in foreign countries or return to the Russian Federation. The state policy of the Russian Federation regarding compatriots abroad is implemented in two opposite directions, which significantly reduces its effectiveness. The mechanisms for implementing this policy are various forms of horizontal and vertical cooperation and interaction in various fields such as humanitarian, social, educational, cultural, and economic. A significant number of policy implementation entities required the creation and use of modern mechanisms for coordinating their activities. The resources spent on the return of compatriots to their homeland are not able to compensate for the emigration outflow from Russia, however, mechanisms aimed at solving the latter problem are not provided. In fact, the local population is excluded from the scope of this policy, which entails a number of problems associated not only with the attitude of the host society towards the migrants, but also with the desire of a significant part of the youth to leave Russia. Keywords: state policy, compatriots, institutions